1982
DOI: 10.1029/tc001i001p00073
|View full text |Cite
|
Sign up to set email alerts
|

Limits of stresses in continental crusts and their relation to the depth‐frequency distribution of shallow earthquakes

Abstract: Based on published results of experiments on low‐temperature, low‐pressure frictional sliding and creep at higher temperature and pressure, theoretical curves of yield strength versus depth corresponding to maximum crustal stresses (STRESSMAX) are calculated. These curves are compared to the frequency‐depth distribution of earthquakes (DEFREQ) in several tectonic areas. Both sets of curves have a very similar form and show a prominent peak. From the similarity it is concluded that it is basically the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
188
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(205 citation statements)
references
References 28 publications
13
188
0
4
Order By: Relevance
“…If it is assumed that a seismic -aseismic boundary is related to the brittle -ductile boundary of the crust (e.g., Sibson, 1982;Meissner and Strehlau, 1982), changes in seismogenic thickness might be expected in the area under study. Constructed rheological profiles indicate that the Central System's southern border acts as a limit between rheological domains.…”
Section: Discussionmentioning
confidence: 99%
“…If it is assumed that a seismic -aseismic boundary is related to the brittle -ductile boundary of the crust (e.g., Sibson, 1982;Meissner and Strehlau, 1982), changes in seismogenic thickness might be expected in the area under study. Constructed rheological profiles indicate that the Central System's southern border acts as a limit between rheological domains.…”
Section: Discussionmentioning
confidence: 99%
“…For brittle failure or frictional sliding the stress energy increases with depth [Sibson, 1982], and a maximum in seismicity is often observed just above the base of the inferred seismogenic zone [Meissner and Strehlau, 1982 …”
Section: Methodsmentioning
confidence: 99%
“…Independently, Meissner and Strehlau [1982] and Chen and Molnar [1983] suggested that reduced seismic activity of the lower crust indicates low ductile flow strength relative to the upper crust. However, mechanical data and flow law parameters on the rheology of rocks typical for the lower crust, i.e., gabbros, metabasites, etc., are still scarce [Caristan, 1982;Shelton and Tullis, 1981;Kirby, 1983;Carter and Tsenn, 1987;Mackwell et al, 1998].…”
Section: Introductionmentioning
confidence: 99%